A deep‐sea sulfate‐reducing bacterium generates zero‐valent sulfur via metabolizing thiosulfate. Issue 3 (23rd September 2022) - Liu, Rui; Shan, Yeqi; Xi, Shichuan; Zhang, Xin; Sun, Chaomin
Abstract: Zero‐valent sulfur (ZVS) is a crucial intermediate in the sulfur geobiochemical circulation and is widespread in deep‐sea cold seeps. Sulfur‐oxidizing bacteria are thought to be the major contributors to the formation of ZVS. However, ZVS production mediated by sulfate‐reducing bacteria (SRB) has rarely been reported. In this study, we isolated and cultured a typical SRB designated Oceanidesulfovibrio marinus CS1 from deep‐sea cold seep sediment in the South China Sea. We show that O. marinus CS1 forms ZVS in the medium supplemented with thiosulfate. Proteomic and protein activity assays revealed that thiosulfate reductase (PhsA) and the sulfide:quinone oxidoreductase (SQR) played key roles in driving ZVS formation in O. marinus CS1. During this process, thiosulfate firstly was reduced by PhsA to form sulfide, then sulfide was oxidized by SQR to produce ZVS. The expressions of PhsA and SQR were significantly upregulated when O. marinus CS1 was cultured in a deep‐sea cold seep, strongly indicating that strain CS1 might form ZVS in the deep‐sea environment. Notably, homologs of phsA and sqr were widely identified from microbes living in sediments of deep‐sea cold seep in the South China Sea by the metagenomic analysis. We thus propose that SRB containing phsA and sqr genes potentially contribute to the formation of ZVS in deep‐sea cold seep environments. Impact statement: In this study, we report a novel zero‐valent sulfur (ZVS) production pathway in a deep‐sea sulfate‐reducing bacterium (SRB) via thiosulfate metabolism. Through genome, proteome, and in vitro protein function verification and other experiments, we have confirmed that this ZVS‐producing process is mainly comprised of thiosulfate reduction by PhsA and sulfide oxidation by quinone oxidoreductase. ZVS is abundant in deep‐sea cold seep ecosystems, which has been reported to be mainly produced by sulfur‐oxidizing bacteria. However, the role of SRB in the production of ZVS has been overlooked. Our findings are important for explaining the formation of ZVS in deep‐sea cold seep sediment.